The second Ottoman Empire : political and social transformation in the early modern world - Tezcan, Baki.; Cambridge University Press (New York : Cambridge University Press, 2012)
"Although scholars have begun to revise the traditional view that the seventeenth and eighteenth centuries marked a decline in the fortunes of the Ottoman Empire, Baki Tezcan's book proposes a radical new approach to this period. While he concurs that decline did take place in certain areas, he constructs a new framework by foregrounding the proto-democratization of the Ottoman polity in this era. Focusing on the background and the aftermath of the regicide of Osman II, he shows how the empire embarked on a period of seismic change in the political, economic, military, and social spheres. It is this period--from roughly 1580 to 1826--that the author labels "the second empire," and that he sees as no less than the transformation of the patrimonial, medieval, dynastic institution into a fledgling limited monarchy. The book is essentially a post-revisionist history of the late Ottoman Empire that will make a major contribution not only to Ottoman scholarship but also to comparable trends in world history"--Provided by publisher.
-- Introduction: Ottoman political history in the early modern period -- One market, one money, one law : the making of an imperial market society and a law that applies to all -- The question of succession : bringing the dynasty under legal supervision -- The court strikes back : the making of Ottoman absolutism -- A new empire for a second Osman : Osman II in power (1618-1622) -- The absolutist dispensation overturned : a regicide -- The second empire goes public : the age of the Janissaries -- Conclusion: Early modernity and the Ottoman decline.
First published 2010.
Includes bibliographical references and index.
Keywords: Osman -- II, -- Sultan of the Turks, -- 1603-1622 -- Assassination; Janizaries -- History; Social change -- Turkey -- History -- 17th century; Social change -- Turkey -- History -- 18th century; Democratization -- Turkey -- History -- 17th century; Turkey -- History -- 1453-1683; Turkey -- History -- 1683-1829.; Turkey -- Politics and government; Turkey -- Economic conditions